A conceptual framework for the ethical analysis of moral conflicts in migrant live-in care - von Kutzleben, Milena; Weßel, Merle; Ulitsa, Natalie; Nebowsky, Anna-Eva; Ayalon, Liat; Schweda, Mark (Frontiers in Psychiatry, 2025)
In many industrialized countries, hiring a migrant live-in carer represents a promising solution to support families caring for an older person at home and to avoid institutionalization. Migrant live-in carers live in the household of the person in need of care and provide extensive care and social support. They usually come from geographic areas such as Eastern Europe or Southeast Asia. Due to often unclear legal regulations regarding labor and migration status, as well as contradicting expectations and entangled vulnerabilities within the triad of the person in need of care, the live-in carer, and the family, these live-in care arrangements are prone to a variety of moral conflicts that require ethical analysis. This article proposes a conceptual ethical framework for analyzing moral conflicts within live-in care arrangements. By recognizing and addressing these conflicts within the multi-level ethical framework, the ground for a triadic perspective is laid and the ethical discussion around live-in care for older people can be put on an empirical basis. This can help to inform counselling and support for these arrangements, as well as policy advice for ethical solutions and improved caregiving practices.